Revisiting exit block after entrance block: Investigation of ablation index‐guided pulmonary vein isolation. Issue 2 (5th January 2023) - Nakashima, Takashi; Nagase, Masaru; Shibahara, Taro; Ono, Daiju; Yamada, Takehiro; Tanabe, Gen; Suzuki, Keita; Yamaura, Makoto; Ido, Takahisa; Takahashi, Shigekiyo; Okura, Hiroyuki; Aoyama, Takuma
Abstract: Introduction: Unidirectional block, left atrium to pulmonary vein (LA‐PV) entrance block without PV‐LA exit block, has not been fully investigated in the setting of ablation index (AI)‐guided pulmonary vein (PV) isolation (PVI). The aim of this study was to investigate unidirectional blocks during AI‐guided PVI. Methods: After achieving entrance block, exit block was evaluated by pacing from the catheter placed in the PV. Local PV musculature capture without conduction to the LA was necessary to prove exit block. Results: In total, 441 PVs (including nine left common PVs) from 113 consecutive patients (mean age: 71 ± 12 years, 77 men, 61 paroxysmal atrial fibrillation cases) who underwent initial AI‐guided PVI for atrial fibrillation were studied. Entrance block was achieved in all PVs. of the 247/441 (56%) PVs showing local PV musculature capture, 5/247 (2.0%) showed unidirectional blocks. Three of the five PVs (left superior and inferior PVs in one patient; right superior PV in another patient) showed LA‐PV reconnection, requiring additional ablation to achieve bidirectional block during the procedure. Two of the five PVs (left superior and inferior PVs in one patient) showed LA‐PV reconnection, and thereafter, LA‐PV conduction became blocked again spontaneously, leading to bidirectional block without further ablation during the procedure. Conclusion: AI‐guided PVI presented a low prevalence of unidirectional block (2%), using entrance block alone as the endpoint of PVI could therefore be justified.